Enhancement of software project performance by overcoming waste, volatility and constraints simultaneously - Siti Aissah, Mad Ali (2019)
There have been many projects and researches conducted to identify software projects’ failure and success factors. The success factors were always remained as best practices as it favours desired results while the failure factors are always avoided as it yields undesired factors. However, it is least understood that focusing on avoiding a failure factor could actually influence other forms of failure risk(s). In this study, it has been understood through literature review that most of the findings on software projects failure factors have been repetitive for more than two decades. These failure factors commonality was then understood and categorized by bridging few studies and experts’ opinions based on three well-known theories; Lean, Requirement Volatility and Theory of Constraints. There are nine types of wastes, three types errors that leads to requirement volatility and eight types of constraints in relevance to software projects. Through literature and discussion with 15 experts it was apparent that there could be interdependency and interrelationship amongst these 20 variables. The relationship amongst the variables were studied by employing the DEMATEL methodology. DEMATEL was opted to show the Impact Relation Map which could serve as a good source of reference to help decision makers formulate their decisions pertaining these 20 variables. A Software Project Success Framework was then developed to assist the foundation for planning and prioritizing relevant mitigations and corrective measures about software projects failure factors. Requirement volatility has been emphasized as the main cause of software project failure. It does not only cause direct impact towards software projects failure but also influences other identified factors to affect the sotware project performance adversely.